Malaysian perspective on human rights - Rohaida Nordin, (Fakulti Undang - Undang, 2010)
The international law has developed and recognised minimum international standards on human rights. It is however important to consider how they actually affect the lives of the human beings in question. Hence, protection under international law includes the issue of States taking the action necessary to implement the law at the domestic level. However, is there any legal obligation for Malaysia to implement international standards? This article will address the issue of whether the Malaysian government could argue that there is nothing to compel the State to comply with the minimum international standards on human rights, argument of which is rooted to its perspective on human rights. This article will demonstrate the Malaysian government’s perspective on human rights that involves the rejection of universal human rights as a Western concept, and the adoption of Asian values. The Malaysian government has also argued that international standards of human rights are not applicable to Malaysia because of the over-emphasis on the rights of the individual as opposed to the rights of the community. International standards of human rights, for example the Universal Declaration on Human Rights, also givegreater priority to civil and political human rights, and are thus alien to Malaysian traditions and cultures. Thus, rights and freedoms of individual in Malaysia will be protected or violated because of what exists or what is lacking within the State and not because of what is said or done within international law and international institutions. An international regime on the nature of human rights can offer no more than guiding principles concerning the protection of individual in Malaysia